PENGARUH KUALITAS KOMUNIKASI TERHADAP SOCIAL LOAFING YANG DIMODERASI OLEH KONTROL DIRI PADA MAHASISWA UNIVERSITAS PENDIDIKAN INDONESIA - Rike Agustina Nuryanto, - (2020)
This research is aimed to determine the effect of quality of communication on social loafing moderated by self-control for students. This research uses a quantitative approach. The sample of this research was 392 Universitas Pendidikan Indonesia students using probability sampling method with proportionate stratified random sampling technique. This research was conducted by using three research instruments: Communication Survey Scale, Self-Control Scale and Social Loafing Scale instrument which has been modiefied by Atikah. The result show there is influence of quality of communication on social loafing with the self-control as a moderating variable for student at Universitas Pendidikan Indonesia. This study shows that the variable of self-control is the type of quasi moderator.